DESIGN AND THE MECHANICAL PROPERTIES STUDY OF A SWING-STYLE OFFICE LOUNGE CHAIR - ZHANG DongDong; QIN BaoRong; WANG ZhengXing; LIU Lei; XIANG BingLe; ZHOU Hui (Jixie qiangdu)
Aiming at the motion request of spine and joints of these people who always sit in the office and according to the theory of ergonomics,a swing-style office lounge chair was designed. According to the testing standard of ANSI / BIFMA,static structure analysis and transient structure analysis was done under the environment of ANSYS Workbench. The stress and strain of the structure were calculated under the function load and proof load. The prototypes were made and tested,and the satisfied results were gotten. The research results indicate that the structure designed can meet the mechanical performance requirements of BIFMA,and the test results consistent with the analysis result. That verifies the accuracy and validity of the analysis,and it will benefit to shortening the development cycles and reducing development costs. The research results also offer important basis for the later structure optimization.